Finding Hidden Outliers to Promote the Consistency of Key Morphological Traits and Phylogeny in Dennstaedtiaceae - Ting Wang; Li Liu; Jun-Jie Luo; Yu-Feng Gu; Si-Si Chen; Bing Liu; Hui Shang; Yue-Hong Yan (Taxonomy, 2021)
With the development of open science and technological innovation, using sharing data and molecular biology techniques in the study of taxonomy and systematics have become a crucial component of plants, which undoubtedly helps us discover more hidden outliers or deal with difficult taxa. In this paper, we take Dennstaedtia smithii as an example, based on sharing molecular database, virtual herbarium and plant photo bank, to clarify the outliers that have been hidden in Dennstaedtia and find the key morphological traits with consistent of molecular systematics. In molecular phylogenetic analyses, we used rbcL, rps4, psbA-trnH and trnL-F sequences from 5 new and 49 shared data; the results showed that Dennstaedtia smithii is nested within Microlepia rather than Dennstaedtia. We further studied the morphological characters based on the phylogeny result and found that D. smithii is distinguished from other species of Dennstaedtia by spore ornamentation and the unconnected of grooves between rachis and pinna rachis. According to morphological and molecular phylogenetic studies, our results supported that D. smithii should be a new member of Microlepia and renamed Microlepia smithii (Hook.) Y.H. Yan. Finding hidden outliers can promote the consistency of morphological and molecular phylogenetic results, and make the systematic classification more natural.